The Role of Baznas, Semarang City in Empowering Productive Zakat In The Zchicken Msme Program, Semarang City - Sarah Maulina; M. Rizal Hanafi; Rosida Dwi Ayuningtyas (Universitas Wahid Hasyim, 2023)
Regulation of the Ministry of Religion of the Republic of Indonesia No. 52 of 2014 specifically explains the techniques for managing productive zakat funds, in this case all operational systems carried out by amil institutions refer to these regulations. The National Amil Zakat Agency or often referred to as BAZNAS is one of the institutions that manages zakat. BAZNAS Semarang City is one of the amil bodies that manages zakat, BAZNAS Semarang City has many programs in its collection, management and distribution. With regard to productive zakat, BAZNAS Semarang City utilizes these funds through the ZChicken business program which is intended for mustahik in improving welfare as well as developing MSMEs. In this study using qualitative methods, the data collection methods used include observation, interviews and documentation. The data obtained, analyzed using descriptive methods. The results of this study indicate that the program organized by BAZNAS Semarang City has been quite effective in utilizing productive zakat to increase MSMEs, the role of BAZNAS Semarang City is also very supportive and has a positive impact by holding training and evaluation every month. The results of this study are the need for collaborative synergy between mustahik ZChicken MSME actors and the amil agency to achieve optimization of the welfare of ZChicken MSME mustahik actors.